Synthesis, stability and printing properties of a novel 2‐sulphophenoxy‐4‐chloro‐s‐triazine reactive dye for ink‐jet printing of wool. (5th February 2020) - Faisal, Saira; Lin, Long; Clark, Matthew
Abstract: We report here the synthesis and characterisation of a new medium‐reactivity reactive dye containing 2‐sulphophenoxy‐4‐chloro‐s‐triazine, having enhanced the activity of the chlorine atom for further substitution by the functional groups carried by wool fibre. In addition, a dichloro‐s‐triazine dye was also synthesised for the purpose of comparison. The progress of synthesis reactions and purity of the dyes were determined using capillary electrophoresis and thin layer chromatography. The molecular structure and the chemical compositions of the synthesised dyes were confirmed using Fourier Transform–infrared spectral data and elemental analyses. The inks containing the synthesised dyes were formulated and ink‐jet‐printed onto wool fabrics and then the printed fabrics were steamed at 102°C. Compared with the dichloro‐s‐triazine dye, superior performance in terms of ink stability, K/S and dye fixation was observed for the new 2‐sulphophenoxy‐4‐chloro‐s‐triazine dye. In addition, the light fastness of the fabric printed with the inks containing the new dye was 0.5‐grade greater than that of the fabric printed with the inks containing the dichloro‐s‐triazine dye, and no changes in shade and staining were observed following wash fastness tests of the fabrics printed with the inks containing the new dye.